AI's Transformative Impact on Healthcare and Medical Research in Pakistan: AI's Transformative Impact on Healthcare and Medical Research in Pakistan (Journal of Fatima Jinnah Medical University, 2025)
Artificial intelligence (AI) has been emerged as a transformative force in the ever-evolving prospect of healthcare bringing unparalleled advancements in patient management and care.1 Rapid unfolded benefits have revolutionized the landscape of healthcare delivery system. Accuracy of diagnostics in clinical, pathological and radiological settings, remote patient monitoring, shared decision-making,1,2 precision medicine,  biomedical literature,  genomic, therapeutics and drug optimization, and health system management through algorithms, data analysis and predictions.2-3          What started as Enigma in 1942, was coined as ‘Artificial Intelligence in 1956 by John McCarthy in the Dartmouth Conference. However, initially it was limited to data computing and research, through neural networks and machine learning (ML), Natural Language Process (NLP), it found its way to daily lives of many through virtual assistants, such as Apple’s Siri and Amazon’s Alexa.1 Usage in health care system through automation and robotic surgery, its role in virtual health care assistant, physical and mental health support, patients’ education  and mitigation of burn out in health care providers, paved the way for its generalization  among end users. A recent study in the USA showed that although more than half of participants felt discomfort with care providers using AI, still 80% of them expressed their willingness to use AI-powered tools to help manage their health themselves.4
Keywords: AI's Transformative